Basal cell carcinoma of the umbilicus associated with sweat gland structures: Two case reports. Issue 8 (22nd February 2023) - Kurosaki, Yukiho; Itoi-Ochi, Saori; Ota, Asako; Miyazaki, Akiko; Kato, Hiroko; Nojima, Satoshi; Morii, Eiichi; Yokoi, Kazunori; Fujimoto, Manabu; Tanemura, Atsushi
Abstract : Rationale: Basal cell carcinoma (BCC) arising in the umbilicus is relatively rare, and in particular, there have been few reports mentioning peritumoral sweat gland structures histopathologically. We herein, report 2 cases of umbilical BCC with sweat gland structures within and around the tumor. Patient concerns: A 61-year-old woman had a 2-year history of black exudative plaque in her umbilicus, and an 80-year-old woman had a 6-month history of dark brownish plaque in the umbilicus, with exudation 2 months prior to her first visit. Diagnoses: Based on the histopathological finding, both cases were confirmed as BCC. The results of immunohistochemical staining showed that the tumor cells were Ber-EP4 positive. In addition, EMA-positive glandular structures were seen within and around the tumor. Interventions: Curative resection at the level of the linea alba on the bottom side was performed. Outcomes: No relapse has been observed since resection in either patient. Lessons: We herein report 2 cases of umbilical BCC with sweat glands and ducts. Although whether peri- and/or intra-tumor sweat gland structures are the source of the tumor or arise by transdifferentiation from tumor cells remains unclear, these findings may provide clues to help understand the morphopathogenesis of umbilical BCC in the future.